The Importance of Action Learning in Higher Education - Azadovna, Abdullaeva Saboxon; Inatullaevna, Namazova Gulnoza (European Journal of Life Safety and Stability (2660-9630), 2021)
Modern Teaching Technologies are necessary for students as well as teachers. Therefore it is necessary to prepare them for the age of Modern Teaching Technology. Student-centered methods contain a great number of various instructional methods, for example project-based learning, problem-based learning, just-in-time teaching, and discussion methods. All these methods are inductive, based on constructivist approach. Action learning is not one specific teaching method, but rather a philosophy and an approach which encourages action within a team environment where learning is every participant’s job. All action learning approaches are philosophically rooted in theories of learning from experience, as practiced collaboratively with others through some form of action research.